Brazilian High School Girls: What Drives Their Career Choices? - Nakamura, Fabíola (2017)
Women represent 30% of the workforce in technological areas. Those statistics are a challenge to gender equality, but pose as an opportunity to engage more people to the cause of bringing more girls to IT areas. This paper shows the results of a survey submitted to high school female students during a career event. Girls answered questions about their high school preferences, their career choices, and what made them choose the area. Results show math is a well-liked subject in High School but girls choose careers in Human or Biological fields. According to them, they lack mathematical skills and vocation to aspire a career in IT.